A Genome-Wide Analysis of Long Noncoding RNAs in Circulating Leukocytes and Their Differential Expression in Type 1 Diabetes Patients - Yihan Liu; Xiaoming Du; Jia Cui; Changlong Li; Meng Guo; Jianyi Lv; Xin Liu; Jingtao Dou; Xiaoyan Du; Hongjuan Fang; Zhenwen Chen (Journal of Diabetes Research)
Long noncoding RNAs (lncRNAs) regulate gene expression at different levels in various diseases, including type 1 diabetes (T1D). However, the expression of circulating lncRNAs in leukocytes in T1D has not been well documented. To identify differentially expressed lncRNAs between T1D patients and healthy controls, RNA sequencing was performed on samples of leukocytes collected from both healthy persons and T1D patients. The categories, enriched pathways, coexpression networks, and the characteristics of novel lncRNAs were analyzed to provide an extensive profile. qPCR was adopted to validate the differential expression of lncRNAs in the validation cohort. A total of 14,930 lncRNAs and 16,063 mRNAs were identified in the peripheral blood leukocyte of T1D patients. After optimization using an adjusted p value (threshold of <0.05), 393 circulating lncRNAs were identified, of which 69 were downregulated and 324 were upregulated in T1D patients. Gene Ontology analysis indicated that these lncRNAs and mRNAs were enriched in the immune system category. Further analysis showed that 61.28% of the novel lncRNAs were conserved in humans. A set of 12 lncRNAs were selected for qPCR validation, and 9 of 12 lncRNAs were confirmed to show significant differential expression between the T1D and control validation cohorts. Among the 9 confirmed lncRNAs, lncRNA MSTRG.128697 and lncRNA MSTRG.128958 were novel and human-specific; however, further validation is required. lncRNA MSTRG.63013 has orthologous sequences in the mouse genome and was identified as a key node for etiology and pathophysiology in animal studies, which will help understand the epigenetic mechanisms of T1D complications.